2023
DOI: 10.3390/polym15092120
|View full text |Cite
|
Sign up to set email alerts
|

Periquiteira (Cochlospermum orinocense): A Promising Amazon Fiber for Application in Composite Materials

Abstract: Natural lignocellulosic fibers (NLFs) have in recent decades appeared as sustainable reinforcement alternatives to replace synthetic fibers in polymer composite material applications. In this work, for the first time, the periquiteira (Cochlospermum orinocense), a lesser known NLF from the Amazon region, was analyzed for its density and, by X-ray diffraction (XRD), to calculate the crystallinity index as well as the microfibrillar angle (MFA), thermogravimetric analysis (TGA), Fourier transform infrared spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 69 publications
(126 reference statements)
0
8
0
Order By: Relevance
“…The event between 240 and 480 • C was attributed to starch and cellulose decomposition. The samples CS-5 and CS-6 exhibited a more pronounced mass loss in the interval between 130 and 300 • C. This characteristic of thermal decomposition has been attributed to three factors: (a) the elimination of glycerol, which has a higher content in these samples; (b) the glycerol also acts by reducing the interaction between the starch chains associated with it; and (c) thermal decomposition of cellulose [4,38,51]. Figure 5 displays the TG and DTG curves for the composite films.…”
Section: Thermogravimetric Analysismentioning
confidence: 93%
See 1 more Smart Citation
“…The event between 240 and 480 • C was attributed to starch and cellulose decomposition. The samples CS-5 and CS-6 exhibited a more pronounced mass loss in the interval between 130 and 300 • C. This characteristic of thermal decomposition has been attributed to three factors: (a) the elimination of glycerol, which has a higher content in these samples; (b) the glycerol also acts by reducing the interaction between the starch chains associated with it; and (c) thermal decomposition of cellulose [4,38,51]. Figure 5 displays the TG and DTG curves for the composite films.…”
Section: Thermogravimetric Analysismentioning
confidence: 93%
“…Figure 2 shows the spectra for fibers without treatment, fibers with alkaline treatment and bleaching, and TPS films with the three amounts of glycerol. The FTIR spectrum for the untreated fibers revealed the presence of a band around 3330 cm −1 , which occurs due to the presence of OH groups of polysaccharides [38]. The bands observed in the range from 2990 to 2820 cm −1 are attributed to C-H bonds that exist in lignin, hemicellulose, and cellulose [39].…”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 98%
“…So far, it is known that the fiber is extracted from the inner bark of the fruit and is commonly used in rope manufacturing. The only studies found in the literature on the properties of periquiteira fibers are the works of [258,259]. The study conducted by Silva et al [258] was the first to analyze the properties of periquiteira fibers, including the composition of lignocellulosic components and mechanical properties through tensile tests.…”
Section: Periquiteiramentioning
confidence: 99%
“…The only studies found in the literature on the properties of periquiteira fibers are the works of [259,260]. The study conducted by Silva et al [259] was the first to analyze the properties of periquiteira fibers, including the composition of lignocellulosic components and mechanical properties through tensile tests. The results of this study are presented in Table 10.…”
Section: Periquiteiramentioning
confidence: 99%
See 1 more Smart Citation